Pengaruh Inklusi Keuangan, Kepuasan Layanan, Pengetahuan Bunga, dan Penguasaan Teknologi Terhadap Akses Pinjaman Online - Benanditha Kurnia Ratri; Purwo Adi Wibowo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research aims to analyze the influence of financial inclusion, service satisfaction, knowledge of interest, and mastery of technology on online loan access for PT employees. Hwaseung Indonesia. In this research, a quantitative approach was used with a population of 5.000 PT employees. Hwaseung Indonesia then took samples using a purposive sampling technique so that a sample of 100 employees was obtained from the population. Data was collected using a questionnaire specifically designed to assess these variables, then analyzed using a regression model with the help of SPSS software. The research results indicate that the variables financial inclusion and service satisfaction have no effect on online loan access because the calculated t value is < 0,1985 and the significance probability value is > 0,05. On the other hand, knowledge of interest influences access to online loans with a calculated t value of 2,995 with a significance probability value of 0,003 and mastery of technology has a significant influence on employees' decisions to access online loans with a calculated t value of 3,249 and a significance probability value of 0,002. These findings indicate that a better understanding of loan interest rates and technology skills are critical in increasing the accessibility of online loan services. This research provides important insights for companies and financial service providers to improve financial literacy and technology skills among employees, to encourage wiser and more responsible use of online loan services.